Respostas

2014-02-05T20:16:45-02:00
A)
Δ = b² -4ac
Δ = 0² -4 *16 * (-9)
Δ = 0 + 576
Δ = 576
x' = (-b + √∆)/ 2a
(-0 + 24)/2 * 16
(0 + 24)/32
24/32
0,75
x'' = (-b - √∆)/ 2a
(-0 - 24)/2 * 16
(0 - 24)/32
-24/32
-0,75

b)
Δ = b² -4ac
Δ = (-5)² -4 *(-20) * 0
Δ = 25 0
Δ = 25
x' = (-b + √∆)/ 2a
(-(-5) + 5)/2 * (-20)
(5 + 5)/-40
10/-40
-0,25
x'' = (-b - √∆)/ 2a
(-(-5) - 5)/2 * (-20)
(5 - 5)/-40
0/-40
0

c)
x²-1=0
x²=1
x=√1
x= +1, -1

d)
Δ = b² -4ac
Δ = (-2)² -4 *7 * 0
Δ = 4 0
Δ = 4
x' = (-b + √∆)/ 2a
(-(-2) + 2)/2 * 7
(2 + 2)/14
4/14
x'' = (-b - √∆)/ 2a
(-(-2) - 2)/2 * 7
(2 - 2)/14
0/14
0
1 4 1